PENGGUNAAN PLATFORM CANVA SEBAGAI PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATERI HADIS TENTANG SABAR - Lucky Maulidha; Dartim Dartim (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
The aim of this research is to describe the use of the Canva platform as an application of the project-based learning model in hadith material about patience for class about patience in class XII-6 at SMA Batik 1 Surakarta. The method used in this research is through a qualitative research approach with data displayed descriptively. The research was conducted on August 1 2023 at SMA Batik 1 Surakarta in class XII-6. The results of this research are that the use of the Canva platform as an application of the project-based learning model on hadith material about patience for class A solid and good group can increase students' self-confidence from the results of the activity of presenting their work to their friends, and students become active in discussing and asking questions. This can show that in conveying Islamic study material, such as the topic of discussing hadith, a project-based learning model can be applied using the Canva platform.